PEMODELAN REGRESI PADA PRODUKTIVITAS KERJA KARYAWAN USAHA FURNITURE BERDASARKAN PENGAWASAN, KEDISIPLINAN, DAN LINGKUNGAN KERJA - Soedjoko, Dodi Kusuma Hadi; Purnomo, Hery; Bhirawa, Sigit Wisnu Setya; Tohari, Amin (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this study was to determine the effect of supervision, discipline and work environment on employee work productivity at VIT Furniture, partially and simultaneously. The results of observations shown that most of the employees often arrive late, often permit during work hours and the work environment is uncomfortable. The research approach used a quantitative descriptive approach, the research sampling technique used a saturated sample, with 40 respondents and analyzed using multiple linear regression. The conclusion of this study is that there is a partial influence between supervision, discipline and work environment on work productivity. And there is a significant effect simultaneously between supervision, discipline, and work environment on work productivity.